Meta-analysis : The Effect of Number Head Together Model on Critical Thinking Ability - Eri Mardiani; YAYAT Suharyat; Mohammad Edy Nurtamam; Tomi Apra Santosa; ilwandri ilwandri (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effect of Number Head Together model on students' critical thinking skills. This type of research is a meta-analysis. The research sample came from 9 national and international journals. The process of searching for data sources through Google Scholar, Plos ONE, Eric, and Wiley. The data source selection method is the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method. Data collection techniques were observation and documentation. Inclusion criteria are national and international journals published in 2015-2023; The type of research must be experimental or quasi-experimental; Data has a relationship with research variables; and Research has the value of t, F and Standard deviation test results. Data analysis used quantitative statistical data analysis by calculating the effect size value with the help of the Comprehensive meta-analysis (CMA) application. The results concluded that the average effect size value of 0.863 was high criteria and the average value of the experimental class was 82.67 while the control class was 70.52 These findings indicate that the Number Head Together (NHT) learning model has a positive effect on students' critical thinking skills